Pengaruh Interaksi Spasial Antara Kota Surakarta dengan Kawasan Perkotaan Sekitarnya Terhadap Pertumbuhan Perkotaan - Sugestiadi, Muhammad Iqbal; Basuki, Yudi (Jurnal Pembangunan Wilayah dan Kota, 2020)
Cities in the systems perspective of cities are related and interconnected with each other. So is in the Subosukawonosraten region which is an Ex-residency region of Surakarta. Both Surakarta City as the administrative city and regency cities in the Subosukawonosraten Region experience interaction due to the needs that cannot be obtained in the origin area. This phenomenon is a symptom that leads to the formation of urban agglomeration which leads to the formation of Surakarta Metropolitan Area. This study aims to determine the effect of spatial interactions between Surakarta City and on urban growth in the Surakarta Metropolitan Area. The analysis carried out included periodic identification of urban growth in the Metropolitan Area, identification of the amount of spatial interaction between Surakarta City and its surrounding urban areas in the Surakarta Metropolitan Area, and analysis of the influence of spatial interactions Surakarta City and its surrounding urban areas on urban growth in the Metropolitan Area Surakarta. The result is that Surakarta City and each urban area has experienced a change in the land area built from 2002 to 2017. The amount of spatial interaction between urban areas in the Surakarta Metropolitan Area and Surakarta City continues to increase. Spatial interaction variables have a significant influence on Boyolali Urban Areas, Karanganyar Urban Areas, and Sukoharjo Urban Areas.